Behavioral Analysis on IPv4 Malware on different platforms in IPv6 Network Environment - M., Zulkiflee; Asmai, S. A.; Nahar, H.; Ayop, Zakiah; Sahib, S. (2011)
Malware is becoming an epidemic in computer network nowadays. Malware attacks are a significant threat to networks. A conducted survey shows malware attacks may result a huge financial impact. This scenario has be-come worse when users are migrating to a new environment which is Internet Protocol Version 6. In this paper, a real Nimda worm was released on a network to further under-stand the worm behavior in real network traffic. A con-trolled environment of IPv6 networks were deployed as a testbed for this study. The result between these two scena-rios on different operating system platforms will be ana-lyzed and discussed further in term of the worm behavior. The experiment result shows that even IPv4 malware still can infect the IPv6 network environment without any mod-ification on the existing malware. In addition, the worm behaves differently in different operating system. A statis-tical approach will be used to validate the result. New detec-tion techniques need to be proposed to remedy this problem swiftly.